Mental Health Effects of Media Exposure Following a Natural Disaster - Julia Frohlich; Angela B. Lindsey; Heidi Radunovich (EDIS)
This document aims to discuss the impacts on mental health that can be intensified via media consumption and to provide media consumption guidelines that can help to monitor media use and decrease negative mental health impacts. Written by Julia Frohlich, Angela B. Lindsey, and Heidi Radunovich, and published by the UF/IFAS Department of Family, Youth and Community Sciences, October 2021.